Calcifying odontogenic cyst: A case report. (15th February 2020) - Mulvihill, C.; Ni Mhaolcatha, S.; Brady, P.; McKenna, J.; Sleeman, D.; Fitzgibbon, J.
Abstract: A calcifying odontogenic cyst (COC) is a rare odontogenic lesion with a vast variety of clinical, radiological, histopathological features and biological behaviours. In this article, we illustrate a case of an 18‐year‐old male patient with a complaint of an 18‐month history of swelling in his right maxilla. The lesion was diagnosed as a COC associated with an impacted 18 using radiological, cytological and histopathological investigations. The present study examines and considers the case.